ANAPHORA ANALYSIS IN UZBEK LANGUAGE TEXTS - Ravshanova Nozima Akhtam (Journals Park Publishing, 2024)
This article describes the study of anaphora abroad, the types of anaphora and the types of anaphora found in Uzbek texts.
Keywords: pragmalinguistics, anaphora, types of anaphora, speech act, anaphoric phrases.